Close-packed silane nanodot arrays by capillary nanostamping coupled with heterocyclic silane ring opening. Issue 43 (9th August 2019) - Philippi, Michael; You, Changjiang; Richter, Christian P.; Schmidt, Mercedes; Thien, Jannis; Liße, Domenik; Wollschläger, Joachim; Piehler, Jacob; Steinhart, Martin
Abstract : We report the parallel generation of close-packed ordered silane nanodot arrays with nanodot diameters of few 100 nm and nearest-neighbor distances in the one-micron range. Abstract : We report the parallel generation of close-packed ordered silane nanodot arrays with nanodot diameters of few 100 nm and nearest-neighbor distances in the one-micron range. Capillary nanostamping of heterocyclic silanes coupled with ring-opening triggered by hydroxyl groups at the substrate surfaces yields nanodots consisting of silane monolayers with exposed terminal functional groups. Using spongy mesoporous silica stamps with methyl-terminated mesopore walls inert towards the heterocyclic silanes, we could manually perform multiple successive stamping cycles under ambient conditions without interruptions for ink refilling. Further functionalizations include the synthesis of polymer nanobrushes on the silane nanodots by surface-initiated atom-transfer radical polymerization. Proteins-of-interest fused to the HaloTag were site-specifically captured to silane nanodots functionalized by copper-free reactions with azide derivatives. Thus, bioorthogonal functionalization for bioanalytics with a spatial resolution in the one-micron range may be realized on solid supports compatible with fluorescence-based optical microscopy. The feature sizes of the silane nanodot arrays match well the length scales characteristic of a variety of biomolecular submicroscopic organizations in living cells, thus representing a compromise between miniaturization and the resolution limit of optical microscopy for sensitive high-throughput bioanalytics.